1996
DOI: 10.1046/j.1365-2249.1996.26736.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nucleosome–IgG immune complexes in ascites from mice transplanted with anti-DNA antibody-secreting hybridomas and in plasmas from MRL-lpr/lpr mice

Abstract: SUMMARYAutoantibodies directed against chromatin components characterize lupus diseases. Immune complexes made of these autoantibodies bound to nucleosomes released from dead cells could play some pathogenic role. The aims of this study were to investigate if nucleosome-IgG complexes could contaminate IgG anti-DNA MoAb preparations, and if such complexes circulate in lupus diseases. A new method was set up using preformed nucleosome-IgG complexes. Complexes were adsorbed onto microplate through Fc binding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Likewise, mouse inoculation with anti-dsDNA and antihistone B cell hybridomas leads to the formation of nucleosome-containing immune complexes in both ascitic fluid and plasma (15,31). These findings illustrate the ability of anti-dsDNA and antihistone lupus antibodies to react, via their respective nucleosomal targets, with nucleosomes.…”
Section: In Vivo Targets Of Lupus Anti-dsdna: From Dsdna To Nucleosomesmentioning
confidence: 76%
“…Likewise, mouse inoculation with anti-dsDNA and antihistone B cell hybridomas leads to the formation of nucleosome-containing immune complexes in both ascitic fluid and plasma (15,31). These findings illustrate the ability of anti-dsDNA and antihistone lupus antibodies to react, via their respective nucleosomal targets, with nucleosomes.…”
Section: In Vivo Targets Of Lupus Anti-dsdna: From Dsdna To Nucleosomesmentioning
confidence: 76%
“…Nonetheless, the presence of circulating DNA(nucleosome? )-anti-DNA immune complexes has been difficult to demonstrate in the past (37,38), and in recent studies with mouse and human sera, direct assessment of such complexes in the circulation (16) or through glomerular basement membrane binding in vitro have revealed low levels of circulating immune complexes (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Kramers et a1 (15) showed that nucleosome-antinucleosome immune complexes bound to the rat glomerular basement membrane when perfused in vivo, while antinucleosome antibodies alone did not. Finally, recent data have demonstrated the presence of nucleosome-IgG complexes in the circulation of 16-28-week-old MRL-lpr/lpr mice (16), a time when kidney lesions are rapidly worsening.…”
mentioning
confidence: 99%
“…One of the major problems with the anti-DNA mAbs is that these IgG may be complexed with nucleosomes (DNA complexed with histones) released from dead cells in the culture supernatant of hybridomas and may give false positive results in assays of cross-reactive binding to several Ags (7,30,31). To assess the purity of the mouse mAbs used, we estimated the possible extent of nucleosome contamination.…”
Section: Purity Of Monoclonal Anti-dna Absmentioning
confidence: 99%